Existence of Periodic Traveling Waves in the Klausmeier Model of Desertification and its Modification: A Comparative Study - Howlader, Md AS; Arif, Md Ariful Islam; Andallah, LS; Gani, M Osman (GANIT: Journal of Bangladesh Mathematical Society, 2018)
Self-organized and spatially periodic banded vegetation patterns have been observed in many semi-arid ecosystems. In order to understand the mechanism of these patterns, we consider a system of reaction-advection-diffusion equations in a two-variable model of desertification. This work deals with the investigation of the existence of periodic traveling waves in a one-parameter family of solutions. In addition, we investigate the existence of periodic traveling waves as a function of water transport parameter in the model. GANIT J. Bangladesh Math. Soc.Vol. 38 (2018) 27-46